Distinct Uroplakin II Staining Pattern in Apocrine Breast Carcinoma. Issue 10 (14th November 2022) - van Pel, Derek M.; Pors, Jennifer; Yuen, Eddie; Chan, Rebecca; Kos, Zuzana; Hayes, Malcolm M.; Wang, Gang
Abstract : Uroplakin II (UPII) has been shown as a highly specific marker of urothelial carcinoma; however, it can also stain subtypes of apocrine-differentiated breast carcinoma. Given that urothelium and breast epithelium share other common immunohistochemical markers, such as CK7 and GATA3, this can lead to a potential diagnostic pitfall. We stained a cohort of triple-negative breast cancer with UPII. Compared with the diffuse, cytoplasmic staining in urothelial carcinoma, UPII was positive in 38.9% of apocrine carcinoma (7/18) with a course, granular cytoplasmic staining pattern and negative in all nonapocrine triple-negative breast cancer cases. Furthermore, the same staining pattern was present in all apocrine metaplasia of the breast (4/4) and apocrine sweat glands in normal skin (6/6). This distinct subcellular localization of UPII staining in breast carcinoma can offer a potential solution to the above diagnostic pitfall.